Amorphous and crystalline solid of bicyclic compound and preparation method thereof

CN119855811APending Publication Date: 2025-04-18SHANGHAI JEMINCARE PHARMACEUTICALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380065090.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-30
Filing Date
2023-09-28
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

In the pharmaceutical manufacturing process, it is difficult for existing technologies to provide solid forms with excellent physical or chemical properties, especially stable and effective crystal forms of bicyclic compounds.

Method used

By preparing different crystal forms A to L of the compound represented by formula (I), using X-ray powder diffraction patterns and other techniques to identify its characteristic diffraction peaks, determine its crystal form and amorphous form, and use various methods such as solvent crystallization, melting, etc. Its stable crystalline and amorphous forms can be obtained through body cooling, anti-solvent flocculation, etc.

Benefits of technology

It realizes the identification and preparation of multiple crystalline and amorphous forms of compounds, improves the stability of their physical and chemical properties, and meets the needs of pharmaceutical manufacturing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119855811A_ABST
    Figure CN119855811A_ABST
Patent Text Reader

Abstract

The invention provides an amorphous form and 16 crystal forms of a compound as shown in a formula (I), and the crystal forms are sequentially named as a crystal form A to a crystal form P. The invention also provides a preparation method of the amorphous form and the polymorphic form of the compound shown in the formula (I). # imgabs0 #
Need to check novelty before this filing date? Find Prior Art

Description

Amorphous and crystalline solids of bicyclic compounds and preparation methods thereof

[0001] This application claims priority to Chinese patent application No. 2022112121001, filed September 30, 2022. This application incorporates the entirety of the aforementioned Chinese patent application. Technical Field

[0002] The present invention belongs to the field of medicinal chemistry, and in particular relates to an amorphous form, a polymorphic form and applications of a bicyclic compound. Background Art

[0003] The industry is looking forward to providing solid forms with excellent physical or chemical properties during the manufacturing process of pharmaceuticals.

[0004] The applicant in this case provided a new CYP51 inhibitor antifungal drug in the patent application with application number PCT / CN2022 / 084203 and application date March 30, 2022, whose structure is shown in formula (I).

[0005] Summary of the Invention

[0006] In one aspect of the present invention, the present invention provides a crystalline form A of the compound represented by formula (I), wherein the X-ray powder diffraction pattern of the crystalline form A has characteristic diffraction peaks at the following 2θ angles: 3.76±0.2°, 5.2±0.2°, 13.75±0.2°, 16.97±0.2°, 17.67±0.2°, and 19.75±0.2°.

[0007] In some embodiments of the present invention, the X-ray powder diffraction pattern of the crystalline form A has characteristic diffraction peaks at the following 2θ angles: 3.76±0.2°, 5.2±0.2°, 5.82±0.2°, 13.75±0.2°, 14.7±0.2°, 16.97±0.2°, 17.67±0.2°, 18.41±0.2°, 19.75±0.2°, and 21.09±0.2°.

[0008] In some embodiments of the present invention, the X-ray powder diffraction pattern of the crystalline form A has characteristic diffraction peaks at the following 2θ angles: 3.76±0.2°, 5.2±0.2°, 5.82±0.2°, 13.07±0.2°, 13.75±0.2°, 14.7±0.2°, 15.85±0.2°, 16.97±0.2°, 17.67±0.2°, 18.41±0.2°, 19.23±0.2°, 19.75±0.2°, 21.09±0.2°, 21.87±0.2°, and 22.92±0.2°.

[0009] In some embodiments of the present invention, the X-ray powder diffraction pattern of the crystalline form A has an X-ray powder diffraction pattern substantially as shown in FIG1 .

[0010] In some embodiments of the present invention, the X-ray powder diffraction pattern analysis data of the crystalline form A is shown in Table 1 below.

[0011] Table 1

[0012] In another aspect of the present invention, the present invention also provides a crystalline form B of the compound represented by formula (I), wherein the X-ray powder diffraction pattern of the crystalline form B has characteristic diffraction peaks at the following 2θ angles: 11.92±0.2°, 16.31±0.2°, 17.75±0.2°, 18.74±0.2°, 19.56±0.2°, and 21.72±0.2°.

[0013] In some embodiments of the present invention, the X-ray powder diffraction pattern of the crystalline form B has characteristic diffraction peaks at the following 2θ angles: 9.88±0.2°, 11.92±0.2°, 16.31±0.2°, 17.19±0.2°, 17.75±0.2°, 18.74±0.2°, 19.56±0.2°, 20.59±0.2°, 21.72±0.2°, and 23.68±0.2°.

[0014] In some embodiments of the present invention, the X-ray powder diffraction pattern of the crystalline form B has characteristic diffraction peaks at the following 2θ angles: 9.88±0.2°, 10.89±0.2°, 11.92±0.2°, 13.11±0.2°, 14.84±0.2°, 16.31±0.2°, 17.19±0.2°, 17.75±0.2°, 18.74±0.2°, 19.56±0.2°, 20.59±0.2°, 21.27±0.2°, 21.72±0.2°, 22.84±0.2°, and 23.68±0.2°.

[0015] [Corrected 29.11.2023 according to Rule 91] In some embodiments of the present invention, the X-ray powder diffraction pattern of the crystalline form B has an X-ray powder diffraction pattern substantially as shown in Figure 3.

[0016] In some embodiments of the present invention, the X-ray powder diffraction pattern analysis data of the crystal form B is shown in Table 2 below.

[0017] Table 2

[0018] In another aspect of the present invention, the present invention also discloses a crystalline form C of the compound represented by formula (I), wherein the X-ray powder diffraction pattern of the crystalline form C has characteristic diffraction peaks at the following 2θ angles: 10.15±0.2°, 11.26±0.2°, 18.24±0.2°, 20.34±0.2°, 20.92±0.2°, and 22.59±0.2°.

[0019] In some embodiments of the present invention, the X-ray powder diffraction pattern of the crystalline form C has characteristic diffraction peaks at the following 2θ angles: 10.15±0.2°, 11.26±0.2°, 14.27±0.2°, 16.57±0.2°, 17.75±0.2°, 18.24±0.2°, 20.34±0.2°, 20.92±0.2°, 22.59±0.2°, and 27.33±0.2°.

[0020] In some embodiments of the present invention, the X-ray powder diffraction pattern of the crystalline form C has characteristic diffraction peaks at the following 2θ angles: 7.04±0.2°, 10.15±0.2°, 10.97±0.2°, 11.26±0.2°, 14.27±0.2°, 16.57±0.2°, 17.75±0.2°, 18.24±0.2°, 20.34±0.2°, 20.92±0.2°, 22.59±0.2°, 23.78±0.2°, 24.87±0.2°, 25.97±0.2°, and 27.33±0.2°.

[0021] [Corrected 29.11.2023 according to Rule 91] In some embodiments of the present invention, the X-ray powder diffraction pattern of the crystalline form C has an X-ray powder diffraction pattern substantially as shown in Figure 5.

[0022] In some embodiments of the present invention, the X-ray powder diffraction pattern analysis data of the crystal form C is shown in Table 3 below.

[0023] Table 3

[0024] In another aspect of the present invention, the present invention provides a crystalline form D of the compound represented by formula (I), wherein the X-ray powder diffraction pattern of the crystalline form D has characteristic diffraction peaks at the following 2θ angles: 4.96±0.2°, 6.65±0.2°, 8.93±0.2°, 13.11±0.2°, 13.85±0.2°, and 17.19±0.2°.

[0025] In some embodiments of the present invention, the X-ray powder diffraction pattern of the crystalline form D has characteristic diffraction peaks at the following 2θ angles: 4.34±0.2°, 4.96±0.2°, 6.65±0.2°, 8.93±0.2°, 13.11±0.2°, 13.85±0.2°, 17.19±0.2°, 17.95±0.2°, 18.84±0.2°, and 20.01±0.2°.

[0026] In some embodiments of the present invention, the X-ray powder diffraction pattern of the crystalline form D has characteristic diffraction peaks at the following 2θ angles: 4.34±0.2°, 4.96±0.2°, 6.65±0.2°, 8.93±0.2°, 13.11±0.2°, 13.85±0.2°, 14.54±0.2°, 15.89±0.2°, 17.19±0.2°, 17.95±0.2°, 18.84±0.2°, 19.4±0.2°, 20.01±0.2°, 22.16±0.2°, and 22.86±0.2°.

[0027] [Corrected 29.11.2023 according to Rule 91] In some embodiments of the present invention, the X-ray powder diffraction pattern of the crystalline form D has an X-ray powder diffraction pattern substantially as shown in Figure 7.

[0028] In some embodiments of the present invention, the X-ray powder diffraction pattern analysis data of the crystal form D is shown in Table 4 below.

[0029] Table 4

[0030] In another aspect of the present invention, the present invention provides a crystalline form E of the compound represented by formula (I), wherein the X-ray powder diffraction pattern of the crystalline form E has characteristic diffraction peaks at the following 2θ angles: 10.42±0.2°, 12.6±0.2°, 16.59±0.2°, 18.24±0.2°, 20.22±0.2°, and 22.42±0.2°.

[0031] In some embodiments of the present invention, the X-ray powder diffraction pattern of the crystalline form E has characteristic diffraction peaks at the following 2θ angles: 10.42±0.2°, 12.6±0.2°, 13.5±0.2°, 16.59±0.2°, 17.71±0.2°, 18.24±0.2°, 20.22±0.2°, 20.88±0.2°, 22.42±0.2°, and 24.11±0.2°.

[0032] In some embodiments of the present invention, the X-ray powder diffraction pattern of the crystalline form E has characteristic diffraction peaks at the following 2θ angles: 3.76±0.2°, 10.42±0.2°, 12.6±0.2°, 13.5±0.2°, 14.51±0.2°, 15.23±0.2°, 16.59±0.2°, 17.71±0.2°, 18.24±0.2°, 20.22±0.2°, 20.88±0.2°, 21.44±0.2°, 22.42±0.2°, 23.5±0.2°, and 24.11±0.2°.

[0033] [Corrected 29.11.2023 according to Rule 91] In some embodiments of the present invention, the X-ray powder diffraction pattern of the crystalline form E has an X-ray powder diffraction pattern substantially as shown in Figure 9.

[0034] In some embodiments of the present invention, the X-ray powder diffraction pattern analysis data of the crystalline form E is shown in Table 5 below.

[0035] Table 5

[0036] In another aspect of the present invention, the present invention also provides a crystalline form F of the compound represented by formula (I), the X-ray powder diffraction pattern of the crystalline form F having characteristic diffraction peaks at the following 2θ angles: 11.94±0.2°, 15.75±0.2°, 18.06±0.2°, 19.27±0.2°, 20.47±0.2°, and 21.39±0.2°.

[0037] In some embodiments of the present invention, the X-ray powder diffraction pattern of the crystalline form F has characteristic diffraction peaks at the following 2θ angles: 3.35±0.2°, 4.11±0.2°, 10.09±0.2°, 11.24±0.2°, 11.94±0.2°, 15.75±0.2°, 18.06±0.2°, 19.27±0.2°, 20.47±0.2°, and 21.39±0.2°.

[0038] In some embodiments of the present invention, the X-ray powder diffraction pattern of the crystalline form F has characteristic diffraction peaks at the following 2θ angles: 3.35±0.2°, 4.11±0.2°, 5.18±0.2°, 5.7±0.2°, 10.09±0.2°, 11.24±0.2°, 11.94±0.2°, 15.75±0.2°, 16.59±0.2°, 18.06±0.2°, 19.27±0.2°, 20.47±0.2°, 21.39±0.2°, 22.46±0.2°, and 24.24±0.2°.

[0039] [Corrected 29.11.2023 according to Rule 91] In some embodiments of the present invention, the X-ray powder diffraction pattern of the crystalline form F has an X-ray powder diffraction pattern substantially as shown in Figure 11.

[0040] In some embodiments of the present invention, the X-ray powder diffraction pattern analysis data of the crystal form F is shown in Table 6 below.

[0041] Table 6

[0042] In another aspect of the present invention, the present invention also provides a crystalline form G of the compound represented by formula (I), wherein the X-ray powder diffraction pattern of the crystalline form G has characteristic diffraction peaks at the following 2θ angles: 5.62±0.2°, 10.58±0.2°, 11.65±0.2°, 14.62±0.2°, 17.67±0.2°, and 21.13±0.2°.

[0043] In some embodiments of the present invention, the X-ray powder diffraction pattern of the crystalline form G has characteristic diffraction peaks at the following 2θ angles: 5.62±0.2°, 10.58±0.2°, 11.65±0.2°, 14.62±0.2°, 15.34±0.2°, 17.67±0.2°, 19.95±0.2°, 20.51±0.2°, 21.13±0.2°, and 21.66±0.2°.

[0044] In some embodiments of the present invention, the X-ray powder diffraction pattern of the crystalline form G has characteristic diffraction peaks at the following 2θ angles: 5.62±0.2°, 9.34±0.2°, 9.8±0.2°, 10.58±0.2°, 11.65±0.2°, 14.62±0.2°, 15.34±0.2°, 17.67±0.2°, 18.61±0.2°, 19.95±0.2°, 20.51±0.2°, 21.13±0.2°, 21.66±0.2°, 23.33±0.2°, and 25.02±0.2°.

[0045] [Corrected 29.11.2023 according to Rule 91] In some embodiments of the present invention, the X-ray powder diffraction pattern of the crystalline form G has an X-ray powder diffraction pattern substantially as shown in Figure 13.

[0046] In some embodiments of the present invention, the X-ray powder diffraction pattern analysis data of the sulfate crystal form G are shown in Table 7 below.

[0047] Table 7

[0048] In another aspect of the present invention, the present invention also provides a crystalline form H of the compound represented by formula (I), wherein the X-ray powder diffraction pattern of the crystalline form H has characteristic diffraction peaks at the following 2θ angles: 10.46±0.2°, 12.47±0.2°, 16.29±0.2°, 18.41±0.2°, 20.26±0.2°, and 21.02±0.2°.

[0049] In some embodiments of the present invention, the X-ray powder diffraction pattern of the crystalline form H has characteristic diffraction peaks at the following 2θ angles: 10.46±0.2°, 11.34±0.2°, 12.47±0.2°, 16.29±0.2°, 17.89±0.2°, 18.41±0.2°, 19.5±0.2°, 20.26±0.2°, 21.02±0.2°, and 22.42±0.2°.

[0050] In some embodiments of the present invention, the X-ray powder diffraction pattern of the crystalline form H has characteristic diffraction peaks at the following 2θ angles: 10.46±0.2°, 11.34±0.2°, 12.47±0.2°, 13.53±0.2°, 16.29±0.2°, 16.97±0.2°, 17.89±0.2°, 18.41±0.2°, 19.07±0.2°, 19.5±0.2°, 20.26±0.2°, 21.02±0.2°, 22.42±0.2°, 24.01±0.2°, and 25.53±0.2°.

[0051] [Corrected 29.11.2023 according to Rule 91] In some embodiments of the present invention, the X-ray powder diffraction pattern of the crystalline form H has an X-ray powder diffraction pattern substantially as shown in Figure 15.

[0052] In some embodiments of the present invention, the X-ray powder diffraction pattern analysis data of the crystalline form H is shown in Table 8 below.

[0053] Table 8

[0054] In another aspect of the present invention, the present invention also provides a crystalline form I of the compound represented by formula (I), wherein the X-ray powder diffraction pattern of the crystalline form I has characteristic diffraction peaks at the following 2θ angles: 9.84±0.2°, 10.37±0.2°, 11.51±0.2°, 20.24±0.2°, 20.71±0.2°, and 22.96±0.2°.

[0055] In some embodiments of the present invention, the X-ray powder diffraction pattern of the crystalline form I has characteristic diffraction peaks at the following 2θ angles: 9.84±0.2°, 10.37±0.2°, 11.51±0.2°, 14.27±0.2°, 17.95±0.2°, 18.3±0.2°, 20.24±0.2°, 20.71±0.2°, 21.25±0.2°, and 22.96±0.2°.

[0056] [Corrected 29.11.2023 according to Rule 91] In some embodiments of the present invention, the X-ray powder diffraction pattern of the crystalline form I has an X-ray powder diffraction pattern substantially as shown in Figure 17.

[0057] In some embodiments of the present invention, the X-ray powder diffraction pattern analysis data of the crystalline form I is shown in Table 9 below.

[0058] Table 9

[0059] In another aspect of the present invention, the present invention also provides a crystalline form J of the compound represented by formula (I), wherein the X-ray powder diffraction pattern of the crystalline form J has characteristic diffraction peaks at the following 2θ angles: 11.67±0.2°, 16.08±0.2°, 16.68±0.2°, 18.86±0.2°, 19.35±0.2°, and 23.74±0.2°.

[0060] In some embodiments of the present invention, the X-ray powder diffraction pattern of the crystalline form J has characteristic diffraction peaks at the following 2θ angles: 9.67±0.2°, 10.91±0.2°, 11.67±0.2°, 16.08±0.2°, 16.68±0.2°, 17.21±0.2°, 18.86±0.2°, 19.35±0.2°, 21.27±0.2°, and 23.74±0.2°.

[0061] In some embodiments of the present invention, the X-ray powder diffraction pattern of the crystalline form J has characteristic diffraction peaks at the following 2θ angles: 5.49±0.2°, 6.3±0.2°, 9.67±0.2°, 10.91±0.2°, 11.67±0.2°, 12.87±0.2°, 14.68±0.2°, 16.08±0.2°, 16.68±0.2°, 17.21±0.2°, 18.86±0.2°, 19.35±0.2°, 20.32±0.2°, 21.27±0.2°, and 23.74±0.2°.

[0062] [Corrected 29.11.2023 according to Rule 91] In some embodiments of the present invention, the X-ray powder diffraction pattern of the crystalline form J has an X-ray powder diffraction pattern substantially as shown in Figure 19.

[0063] In some embodiments of the present invention, the X-ray powder diffraction pattern analysis data of the crystal form J is shown in Table 10 below.

[0064] Table 10

[0065] In another aspect of the present invention, the present invention also provides a crystalline form K of the compound represented by formula (I), wherein the X-ray powder diffraction pattern of the crystalline form K has characteristic diffraction peaks at the following 2θ angles: 12.04±0.2°, 15.85±0.2°, 18.18±0.2°, 19.31±0.2°, 19.56±0.2°, and 21.48±0.2°.

[0066] In some embodiments of the present invention, the X-ray powder diffraction pattern of the crystalline form K has characteristic diffraction peaks at the following 2θ angles: 11.42±0.2°, 12.04±0.2°, 15.85±0.2°, 16.64±0.2°, 18.18±0.2°, 19.31±0.2°, 19.56±0.2°, 20.57±0.2°, 21.48±0.2°, and 24.28±0.2°.

[0067] In some embodiments of the present invention, the X-ray powder diffraction pattern of the crystalline form K has characteristic diffraction peaks at the following 2θ angles: 5.76±0.2°, 10.17±0.2°, 11.42±0.2°, 12.04±0.2°, 15.85±0.2°, 16.64±0.2°, 18.18±0.2°, 18.72±0.2°, 19.31±0.2°, 19.56±0.2°, 20.57±0.2°, 21.48±0.2°, 22.51±0.2°, 24.28±0.2°, and 25.6±0.2°.

[0068] [Corrected 29.11.2023 according to Rule 91] In some embodiments of the present invention, the X-ray powder diffraction pattern of the crystalline form K has an X-ray powder diffraction pattern substantially as shown in Figure 21.

[0069] In some embodiments of the present invention, the X-ray powder diffraction pattern analysis data of the crystal form K is shown in Table 11 below.

[0070] Table 11

[0071] In another aspect of the present invention, the present invention also provides a crystalline form L of the compound represented by formula (I), wherein the X-ray powder diffraction pattern of the crystalline form L has characteristic diffraction peaks at the following 2θ angles: 10.42±0.2°, 12.43±0.2°, 16.27±0.2°, 18.18±0.2°, 20.08±0.2°, and 21±0.2°.

[0072] In some embodiments of the present invention, the X-ray powder diffraction pattern of the crystalline form L has characteristic diffraction peaks at the following 2θ angles: 10.42±0.2°, 11.28±0.2°, 12.43±0.2°, 13.48±0.2°, 16.27±0.2°, 18.18±0.2°, 20.08±0.2°, 21±0.2°, 22.36±0.2°, and 23.91±0.2°.

[0073] In some embodiments of the present invention, the X-ray powder diffraction pattern of the crystalline form L has characteristic diffraction peaks at the following 2θ angles: 3.08±0.2°, 10.42±0.2°, 11.28±0.2°, 12.43±0.2°, 13.48±0.2°, 14.47±0.2°, 16.27±0.2°, 16.82±0.2°, 18.18±0.2°, 20.08±0.2°, 21±0.2°, 22.36±0.2°, 23.91±0.2°, 25.47±0.2°, and 28.15±0.2°.

[0074] [Corrected 29.11.2023 according to Rule 91] In some embodiments of the present invention, the X-ray powder diffraction pattern of the crystalline form L has an X-ray powder diffraction pattern substantially as shown in Figure 23.

[0075] In some embodiments of the present invention, the X-ray powder diffraction pattern analysis data of the crystal form L is shown in Table 12 below.

[0076] Table 12

[0077] In another aspect of the present invention, the present invention also provides a crystalline form M of the compound represented by formula (I), wherein the X-ray powder diffraction pattern of the crystalline form M has characteristic diffraction peaks at the following 2θ angles: 5.33±0.2°, 7.04±0.2°, 14.7±0.2°, 15.85±0.2°, 18.43±0.2°, and 21.11±0.2°.

[0078] In some embodiments of the present invention, the X-ray powder diffraction pattern of the crystalline form M has characteristic diffraction peaks at the following 2θ angles: 4.38±0.2°, 5.33±0.2°, 7.04±0.2°, 14.06±0.2°, 14.7±0.2°, 15.85±0.2°, 17.38±0.2°, 18.43±0.2°, 19.11±0.2°, and 21.11±0.2°.

[0079] In some embodiments of the present invention, the X-ray powder diffraction pattern of the crystalline form M has characteristic diffraction peaks at the following 2θ angles: 4.38±0.2°, 4.87±0.2°, 5.33±0.2°, 7.04±0.2°, 10.6±0.2°, 14.06±0.2°, 14.7±0.2°, 15.85±0.2°, 17.38±0.2°, 18.43±0.2°, 19.11±0.2°, 19.58±0.2°, 21.11±0.2°, 21.78±0.2°, and 27.78±0.2°.

[0080] [Corrected on 29.11.2023 according to Rule 91][Corrected on 29.11.2023 according to Rule 91] In some embodiments of the present invention, the X-ray powder diffraction pattern of the crystal form N has an X-ray powder diffraction pattern substantially as shown in Figure 27.

[0081] [Corrected 29.11.2023 in accordance with Article 91]

[0082] [Corrected 29.11.2023 in accordance with Article 91]

[0083] [Corrected 29.11.2023 in accordance with Article 91]

[0084] [Corrected 29.11.2023 in accordance with Article 91]

[0085] [Corrected 29.11.2023 in accordance with Article 91]

[0086] [Corrected 29.11.2023 in accordance with Article 91]

[0087] In some embodiments of the present invention, the X-ray powder diffraction pattern analysis data of the crystal form N is shown in Table 14 below.

[0088] Table 14

[0089] In another aspect of the present invention, the present invention also provides a crystalline form O of the compound represented by formula (I), wherein the X-ray powder diffraction pattern of the crystalline form O has characteristic diffraction peaks at the following 2θ angles: 5.02±0.2°, 10.29±0.2°, 12.54±0.2°, 16.72±0.2°, 17.62±0.2°, and 20.45±0.2°.

[0090] In some embodiments of the present invention, the X-ray powder diffraction pattern of the crystalline form O has characteristic diffraction peaks at the following 2θ angles: 5.02±0.2°, 10.29±0.2°, 12.54±0.2°, 13.59±0.2°, 15.34±0.2°, 16.72±0.2°, 17.62±0.2°, 19.75±0.2°, 20.45±0.2°, and 25.37±0.2°.

[0091] In some embodiments of the present invention, the X-ray powder diffraction pattern of the crystalline form O has characteristic diffraction peaks at the following 2θ angles: 5.02±0.2°, 10.29±0.2°, 12.54±0.2°, 13.59±0.2°, 14.25±0.2°, 15.34±0.2°, 16.72±0.2°, 17.62±0.2°, 19.75±0.2°, 20.45±0.2°, 20.9±0.2°, 22.61±0.2°, 23.33±0.2°, 25.37±0.2°, and 26.79±0.2°.

[0092] [Corrected 29.11.2023 according to Rule 91] In some embodiments of the present invention, the X-ray powder diffraction pattern of the crystalline form O has an X-ray powder diffraction pattern substantially as shown in Figure 29.

[0093] In some embodiments of the present invention, the X-ray powder diffraction pattern analysis data of the crystal form O is shown in Table 15 below.

[0094] Table 15

[0095] In another aspect of the present invention, the present invention also provides a crystalline form P of the compound represented by formula (I), the X-ray powder diffraction pattern of the crystalline form P having characteristic diffraction peaks at the following 2θ angles: 11.53±0.2°, 14.72±0.2°, 15.98±0.2°, 17.01±0.2°, 17.54±0.2°, and 19.5±0.2°.

[0096] In some embodiments of the present invention, the X-ray powder diffraction pattern of the crystalline form P has characteristic diffraction peaks at the following 2θ angles: 9.57±0.2°, 11.05±0.2°, 11.53±0.2°, 12.82±0.2°, 14.72±0.2°, 15.98±0.2°, 17.01±0.2°, 17.54±0.2°, 19.09±0.2°, and 19.5±0.2°.

[0097] In some embodiments of the present invention, the X-ray powder diffraction pattern of the crystalline form P has characteristic diffraction peaks at the following 2θ angles: 9.57±0.2°, 11.05±0.2°, 11.53±0.2°, 12.82±0.2°, 14.72±0.2°, 15.98±0.2°, 17.01±0.2°, 17.54±0.2°, 19.09±0.2°, 19.5±0.2°, 20.24±0.2°, 20.88±0.2°, 21.43±0.2°, 22.14±0.2°, and 23.89±0.2°.

[0098] [Corrected 29.11.2023 according to Rule 91] In some embodiments of the present invention, the X-ray powder diffraction pattern of the crystalline form P has an X-ray powder diffraction pattern substantially as shown in Figure 31.

[0099] In some embodiments of the present invention, the X-ray powder diffraction pattern analysis data of the crystal form P is shown in Table 16 below.

[0100] Table 16

[0101] Definition and Description

[0102] Unless otherwise defined, all technical and scientific terms used herein have the same meanings as commonly understood by one of ordinary skill in the art to which this invention belongs. All patents and publications to which this invention pertains are incorporated herein by reference in their entirety. Although any methods and materials similar or equivalent to those described herein can be used in the practice or testing of the present invention, the preferred methods, devices, and materials are described herein.

[0103] "API" or "free state" refers to the free base form of the compound represented by formula (I).

[0104] "Crystal form" or "crystalline form" refers to a solid having a highly regular chemical structure, including, but not limited to, single-component or multi-component crystals, and / or polymorphs, solvates, hydrates, inclusion compounds, co-crystals, salts, solvates of salts, and hydrates of salts of a compound. Crystalline forms of a substance can be obtained by a number of methods known in the art. Such methods include, but are not limited to, melt crystallization, melt cooling, solvent crystallization, crystallization in a confined space, for example, in a nanopore or capillary, crystallization on a surface or template, for example, on a polymer, crystallization in the presence of an additive such as a co-crystallizing countermolecule, desolvation, dehydration, rapid evaporation, rapid cooling, slow cooling, vapor diffusion, sublimation, reactive crystallization, antisolvent addition, grinding, and solvent drop grinding, etc.

[0105] "Amorphous" or "amorphous form" refers to a substance formed when the particles (molecules, atoms, ions) are arranged in a three-dimensional space without periodicity, characterized by a diffuse, unsharp X-ray powder diffraction pattern. Amorphous is a special physical form of solid matter, and its locally ordered structure suggests that it is inextricably linked to crystalline forms. Amorphous forms of substances can be obtained by a variety of methods known in the art. Such methods include, but are not limited to, quenching, antisolvent flocculation, ball milling, spray drying, freeze drying, wet granulation, and solid dispersion techniques.

[0106] "Solvent" refers to a substance (typically a liquid) that can completely or partially dissolve another substance (typically a solid). Solvents useful in the practice of the present invention include, but are not limited to, water, acetic acid, acetone, acetonitrile, benzene, chloroform, carbon tetrachloride, dichloromethane, dimethyl sulfoxide, 1,4-dioxane, ethanol, ethyl acetate, butanol, tert-butanol, N,N-dimethylacetamide, N,N-dimethylformamide, formamide, formic acid, heptane, hexane, isopropanol, methanol, methyl ethyl ketone, 1-methyl-2-pyrrolidone, mesitylene, nitromethane, polyethylene glycol, propanol, 2-acetone, pyridine, tetrahydrofuran, toluene, xylene, mixtures thereof, and the like.

[0107] "Anti-solvent" refers to a fluid that promotes precipitation of a product (or product precursor) from a solvent. The anti-solvent can include a cold gas, or a fluid that promotes precipitation by a chemical reaction, or a fluid that reduces the solubility of the product in the solvent; it can be the same liquid as the solvent but at a different temperature, or it can be a different liquid from the solvent.

[0108] "Solvate" refers to a crystal having a solvent on the surface, in the crystal lattice, or both on the surface and in the crystal lattice, wherein the solvent may be water, acetic acid, acetone, acetonitrile, benzene, chloroform, carbon tetrachloride, dichloromethane, dimethyl sulfoxide, 1,4-dioxane, ethanol, ethyl acetate, butanol, tert-butanol, N,N-dimethylacetamide, N,N-dimethylformamide, formamide, formic acid, heptane, hexane, isopropanol, methanol, methyl ethyl ketone, methylpyrrolidone, mesitylene, nitromethane, polyethylene glycol, propanol, 2-propanone, pyridine, tetrahydrofuran, toluene, xylene, and mixtures thereof. A specific example of a solvate is a hydrate, wherein the solvent on the surface, in the crystal lattice, or both on the surface and in the crystal lattice is water. A hydrate may or may not have other solvents other than water on the surface, in the crystal lattice, or both on the surface and in the crystal lattice of the substance.

[0109] Crystalline or amorphous forms can be identified by a variety of technical means, such as X-ray powder diffraction (XRPD), infrared absorption spectroscopy (IR), melting point method, differential scanning calorimetry (DSC), thermogravimetric analysis (TGA), nuclear magnetic resonance, Raman spectroscopy, X-ray single crystal diffraction, dissolution calorimetry, scanning electron microscopy (SEM), quantitative analysis, solubility and dissolution rate, etc.

[0110] X-ray powder diffraction (XRPD) can detect information such as changes in crystal form, crystallinity, and crystalline state, and is a common means of identifying crystal forms. The peak position of the XRPD pattern depends primarily on the structure of the crystal form and is relatively insensitive to experimental details, while its relative peak height depends on many factors related to sample preparation and instrument geometry. Therefore, in some embodiments, the crystal form of the present invention is characterized by an XRPD pattern with certain peak positions, which is substantially as shown in the XRPD pattern provided in the accompanying drawings of the present invention. At the same time, the measurement of 2θ of the XRPD pattern may have experimental errors, and the measurement of 2θ of the XRPD pattern may be slightly different between different instruments and different samples, so the numerical value of the 2θ cannot be considered absolute. According to the instrument conditions used in the test of the present invention, the diffraction peak has an error tolerance of ±0.2°.

[0111] Differential Scanning Calorimetry (DSC) is a technique that measures the energy difference between a sample and an inert reference material (usually α-Al2O3) as a function of temperature by continuously heating or cooling the sample under program control. The height of the melting peak of the DSC curve depends on many factors related to sample preparation and instrument geometry, while the peak position is relatively insensitive to experimental details. Therefore, in some embodiments, the crystal form described in the present invention is characterized by a DSC graph with a characteristic peak position, which is substantially as shown in the DSC graph provided in the accompanying drawings of the present invention. At the same time, DSC spectra may have experimental errors, and the peak positions and peak values ​​of DSC spectra may vary slightly between different instruments and different samples. Therefore, the peak position or peak value of the DSC endothermic peak cannot be considered absolute. According to the instrument conditions used in the test of the present invention, the melting peak has an error tolerance of ±3°C.

[0112] Glass transition refers to the transition of an amorphous material between a highly elastic state and a glassy state, and is an inherent property of the material; its corresponding transition temperature is the glass transition temperature (Tg), which is an important physical property of amorphous materials. Glass transition is a phenomenon related to molecular motion. Therefore, the glass transition temperature (Tg) mainly depends on the structure of the material and is relatively insensitive to experimental details. In some embodiments, the glass transition temperature (Tg) of the amorphous material described in the present invention is measured by differential scanning calorimetry (DSC), and is characterized by having a glass transition temperature of 66°C. According to the conditions of the instruments used in the test of the present invention, the glass transition temperature has an error tolerance of ±3°C.

[0113] Differential scanning calorimetry (DSC) can also be used to detect and analyze whether there is crystal transformation or mixed crystal phenomenon.

[0114] Solids with the same chemical composition often form isomers, or variants, with different crystal structures under different thermodynamic conditions. This phenomenon is called polymorphism or polyphasic phenomenon. When the temperature and pressure conditions change, the variants will transform into each other, which is called crystal transformation. Due to crystal transformation, the mechanical, electrical, magnetic and other properties of the crystal will undergo significant changes. When the temperature of the crystal transformation is within the measurable range, this transformation process can be observed on the differential scanning calorimetry (DSC) graph, which is characterized by having an exothermic peak reflecting this transformation process and two or more endothermic peaks, which are respectively characteristic endothermic peaks of the different crystal forms before and after the transformation. The crystalline form or amorphous form of the compound of the present invention can undergo crystal transformation under appropriate conditions.

[0115] Thermogravimetric analysis (TGA) is a technique that measures the mass change of a substance with temperature under program control. It is suitable for examining the loss of solvent from crystals or the sublimation and decomposition of samples, and can infer the presence of water of crystallization or solvent in the crystals. The mass change shown by the TGA curve depends on many factors, including sample preparation and instrumentation; the mass change detected by TGA varies slightly between different instruments and samples. Based on the instrumentation used in the present test, the mass change has an error tolerance of ±0.3%.

[0116] The moisture adsorption / desorption isotherm (DVS) is a method that measures the adsorption and desorption behavior of water by measuring the weight change of a solid under various relative humidity conditions.

[0117] In the context of the present invention, the 2θ values ​​in the X-ray powder diffraction pattern are all in degrees (°).

[0118] When referring to a spectrum and / or data appearing in a graph, a "peak" refers to a feature that can be identified by one skilled in the art and is not attributable to background noise.

[0119] The term "substantially as shown" means that at least 50%, or at least 60%, or at least 70%, or at least 80%, or at least 90%, or at least 95%, or at least 99% of the peaks in the X-ray powder diffraction pattern or DSC pattern or TGA results are shown in its pattern.

[0120] "Substantially pure" means that one crystalline form is substantially free of one or more other crystalline forms, that is, the purity of the crystalline form is at least 80%, or at least 85%, or at least 90%, or at least 93%, or at least 95%, or at least 98%, or at least 99%, or at least 99.5%, or at least 99.6%, or at least 99.7%, or at least 99.8%, or at least 99.9%, or the crystalline form contains other crystalline forms, and the percentage of the other crystalline forms in the total volume or total weight of the crystalline form is less than 20%, or less than 10%, or less than 5%, or less than 3%, or less than 1%, or less than 0.5%, or less than 0.1%, or less than 0.01%.

[0121] "Substantially free" means that the percentage of one or more other crystalline forms in the total volume or total weight of the crystalline form is less than 20%, or less than 10%, or less than 5%, or less than 4%, or less than 3%, or less than 2%, or less than 1%, or less than 0.5%, or less than 0.1%, or less than 0.01%.

[0122] “Relative intensity” refers to the ratio of the intensity of other peaks to the intensity of the first strongest peak among all diffraction peaks in an X-ray powder diffraction pattern (XRPD) when the intensity of the first strongest peak is 100%.

[0123] In the context of the present invention, when or whether the word "about" or "approximately" is used, it means within 10%, suitably within 5%, and especially within 1% of a given value or range. Alternatively, for those of ordinary skill in the art, the term "about" or "approximately" means within an acceptable standard error of the mean. Whenever a number having a value of N is disclosed, any number having a value of N + / - 1%, N + / - 2%, N + / - 3%, N + / - 5%, N + / - 7%, N + / - 8% or N + / - 10% is expressly disclosed, where "+ / -" means plus or minus.

[0124] The term "comprising" is an open expression, that is, including the contents specified in the present invention, but not excluding other contents. BRIEF DESCRIPTION OF THE DRAWINGS

[0125] FIG1 is an XRPD diagram of Form A according to an embodiment of the present invention;

[0126] FIG2 is an NMR diagram of Form A according to an embodiment of the present invention;

[0127] FIG3 is an XRPD diagram of Form B according to an embodiment of the present invention;

[0128] FIG4 is an NMR diagram of Form B according to an embodiment of the present invention;

[0129] FIG5 is an XRPD diagram of Form C according to an embodiment of the present invention;

[0130] FIG6 is an NMR diagram of Form C according to an embodiment of the present invention;

[0131] FIG7 is an XRPD diagram of Form D according to an embodiment of the present invention;

[0132] FIG8 is an NMR diagram of Form D according to an embodiment of the present invention;

[0133] FIG9 is an XRPD diagram of Form E according to an embodiment of the present invention;

[0134] FIG10 is an NMR diagram of Form E according to an embodiment of the present invention;

[0135] FIG11 is an XRPD pattern of Form F according to an embodiment of the present invention;

[0136] FIG12 is an NMR diagram of Form F according to an embodiment of the present invention;

[0137] FIG13 is an XRPD pattern of Form G according to an embodiment of the present invention;

[0138] FIG14 is an NMR diagram of Form G according to an embodiment of the present invention;

[0139] FIG15 is an XRPD pattern of Form H according to an embodiment of the present invention;

[0140] FIG16 is an NMR diagram of Form H according to an embodiment of the present invention;

[0141] FIG17 is an XRPD pattern of Form I according to an embodiment of the present invention;

[0142] FIG18 is an NMR diagram of Form I according to an embodiment of the present invention;

[0143] FIG19 is an XRPD pattern of Form J according to an embodiment of the present invention;

[0144] FIG20 is an NMR diagram of Form J according to an embodiment of the present invention;

[0145] FIG21 is an XRPD pattern of Form K according to an embodiment of the present invention;

[0146] FIG22 is an NMR diagram of Form K according to an embodiment of the present invention;

[0147] FIG23 is an XRPD pattern of Form L according to an embodiment of the present invention;

[0148] FIG24 is an NMR diagram of Form L according to an embodiment of the present invention;

[0149] FIG25 is an XRPD pattern of Form M according to an embodiment of the present invention;

[0150] FIG26 is an NMR diagram of Form M according to an embodiment of the present invention;

[0151] FIG27 is an XRPD pattern of Form N according to an embodiment of the present invention;

[0152] FIG28 is an NMR diagram of Form N according to an embodiment of the present invention;

[0153] FIG29 is an XRPD pattern of Form O according to an embodiment of the present invention;

[0154] FIG30 is an NMR graph of Form O according to an embodiment of the present invention;

[0155] FIG31 is an XRPD pattern of Form P according to an embodiment of the present invention;

[0156] FIG32 is an NMR diagram of Form P according to an embodiment of the present invention;

[0157] FIG33 is (a) a DVS curve of Form P according to an embodiment of the present invention; (b) XRPD patterns before and after DVS testing;

[0158] FIG34 is a PLM image of Form P according to an embodiment of the present invention;

[0159] FIG35 is an XRPD pattern of an amorphous form according to an embodiment of the present invention;

[0160] FIG36 is an NMR graph of an amorphous form according to an embodiment of the present invention;

[0161] FIG37 is an amorphous (a) DVS curve according to an embodiment of the present invention; (b) XRPD pattern before and after DVS test;

[0162] FIG38 is an amorphous PLM image according to an embodiment of the present invention;

[0163] FIG39 is an XRPD pattern of amorphous stability study according to an embodiment of the present invention;

[0164] FIG40 is an XRPD diagram of a stability study of Form P according to an embodiment of the present invention;

[0165] FIG41 is a comparative XRPD diagram of the solid remaining after the amorphous phase is shaken in a medium for 24 hours according to an embodiment of the present invention;

[0166] Figure 42 is a comparison of XRPD images of the solid remaining after oscillating the crystal form P in a medium for 24 hours according to an embodiment of the present invention. DETAILED DESCRIPTION

[0167] The present application is described in detail below by way of examples, but this does not necessarily mean that there are any adverse limitations on the present application. The present application has been described in detail herein, and specific embodiments thereof have been disclosed. It will be apparent to those skilled in the art that various changes and modifications can be made to the specific embodiments of the present application without departing from the spirit and scope of the present application.

[0168] Unless otherwise specified, the raw materials used in the present invention are commercially available.

[0169] General analytical methods:

[0170] 1. NMR analysis ( 1 H NMR)

[0171] Several milligrams of solid sample were dissolved in dimethyl sulfoxide-d6 solvent and subjected to nuclear magnetic resonance analysis on a Bruker AVANCE NEO 400 (Bruker, Germany).

[0172] 2. X-ray powder diffraction (XRPD)

[0173] The solid samples obtained in the experiment were analyzed using a Bruker D8 Advance X-ray powder diffractometer (Bruker, Germany). The 2θ scan angle ranged from 3° to 45°, with a scan step size of 0.02° and an exposure time of 0.08 seconds. The test method used Cu target Kα1 radiation, a voltage of 40 kV, a current of 40 mA, and a zero-background sample pan.

[0174] 3. Thermogravimetric analysis (TGA)

[0175] The thermogravimetric analyzer (TA Discovery 550, US) was used. A 2-5 mg sample was placed in a equilibrated open aluminum sample pan and automatically weighed in the TGA furnace. The sample was heated to the final temperature at a rate of 10°C / min. A nitrogen purge rate of 60 mL / min was maintained at the sample and 40 mL / min at the balance.

[0176] 4. Differential Scanning Calorimetry (DSC)

[0177] The differential scanning calorimeter was a TA Discovery 250 (TA, US). 1-2 mg of sample was accurately weighed and placed in a perforated DSC Tzero sample pan. The sample was heated to the final temperature at a rate of 10°C / min, with nitrogen purge rate of 50 mL / min.

[0178] 5. Dynamic moisture adsorption and desorption analysis (DVS)

[0179] Dynamic moisture sorption / desorption analysis was performed using a DVS Intrinsic (SMS, UK). The test used a gradient profile with humidity changes from 50% to 95% to 0% to 50%, with each gradient increasing by 10% within the 0% to 90% range. The gradient endpoint was determined using the dm / dt method, with a dm / dt of less than 0.002% maintained for 10 minutes. After completion of the test, the samples were analyzed by XRPD to confirm any changes in the solid form.

[0180] 6. Polarized light microscopy (PLM)

[0181] A polarizing microscope was used, Nikon Ci-POL (Nikon, JP). A small amount of sample was placed on a glass slide and an appropriate lens was selected to observe the sample morphology.

[0182] 7. High Performance Liquid Chromatography (HPLC)

[0183] The high performance liquid chromatography model was SHIMADZU LC-2030C (Shimadzu, JP), and the test conditions were shown in Tables 17 and 18.

[0184] Table 17 HPLC solubility test conditions

[0185] Table 18 HPLC purity test conditions

[0186] General test methods:

[0187] 1. Raw material solubility test

[0188] Weigh approximately 20 mg of sample into an EP tube. Add a defined amount of solvent incrementally at room temperature (~25°C). Stir the solution and observe whether the solid is completely dissolved. If the solid remains insoluble after adding 10.0 mL of solvent, discontinue the experiment. Estimate the solubility of the compound in the solvent based on the volume of solvent used to completely dissolve the solid.

[0189] 2. Solvent evaporation method

[0190] Prepare a clear solution from the raw material solubility test (general test method 1) or weigh about 20 mg of sample (filter the system with solid precipitation) and let it stand open at room temperature until the solvent is completely evaporated to obtain a solid.

[0191] 3. Suspension method

[0192] 3.1. Room temperature suspension

[0193] Different crystal forms are used as raw materials, and a certain amount of sample is added to a selected single solvent or binary solvent until a suspension is formed. After suspension and stirring at room temperature for a certain period of time, the suspension is centrifuged and the solid is vacuum dried at room temperature.

[0194] 3.2, 50℃ suspension

[0195] Using amorphous as raw material, a certain amount of sample is added to the selected solvent until a suspension is formed. After suspension and stirring at 50°C for 24 hours, the suspension is centrifuged and the solid is vacuum dried at room temperature.

[0196] 3.3 Low-temperature suspension

[0197] Using different crystal forms as raw materials, a certain amount of sample was added to the selected binary solvent until a suspension was formed. After suspension and stirring at 10°C for 24 hours, the suspension was centrifuged and the solid was vacuum dried at room temperature.

[0198] 4. Dissolution crystallization method

[0199] 4.1. Binary solvent back titration method

[0200] Weigh approximately 15 mg of sample and add a sufficient amount of good solvent at room temperature to completely dissolve the sample. Add the solution dropwise to 10 times the volume of poor solvent. Stir for 1 hour, centrifuge any solid precipitate, and vacuum dry the solid at room temperature. Continue stirring for 24 hours for the clear solution. If no solid precipitate remains, place the solution in a refrigerator at 4 or -15°C. Centrifuge any solid precipitate, and vacuum dry the solid at room temperature. If no solid precipitate remains, allow the solution to stand at room temperature in the open air until the solvent evaporates completely to yield a solid.

[0201] 4.2. Binary Solvent Forward Drop Method

[0202] Weigh approximately 15 mg of sample and add a sufficient amount of good solvent dropwise at room temperature to completely dissolve the sample. Add a poor solvent dropwise until solid precipitates. Stir at room temperature for 1 hour, centrifuge any solid precipitates, and vacuum dry the solid at room temperature. Continue stirring the clear solution for 24 hours. If no solid precipitates, place the solution in a refrigerator at 4 or -15°C, centrifuge any solid precipitates, and vacuum dry the solid at room temperature. If no solid precipitates, allow the solution to stand at room temperature in the open air until the solvent evaporates completely to yield a solid.

[0203] 5. Binary solvent cooling method

[0204] Weigh about 15 mg of sample and mix it with a certain amount of poor solvent at 50°C to form a suspension. Gradually add preheated good solvent until the solid is completely dissolved, and transfer the solution to room temperature to cool. Let it stand at room temperature for more than 2 hours. If sufficient solid does not precipitate, place the solution at 4°C to cool it further. If sufficient solid still does not precipitate, place the solution at -15°C to cool it further. For systems with sufficient solid precipitation, centrifuge and vacuum dry the solid at room temperature. If there is still no solid precipitation, let the solution stand open at room temperature until the solvent is completely evaporated to obtain a solid.

[0205] Weigh approximately 15 mg of sample and dissolve it in the selected binary solvent at room temperature. Cool the solution to 4°C. If sufficient solid precipitates, cool the solution further to -15°C. For systems where sufficient solid precipitates, centrifuge and vacuum dry the solid at room temperature. If no solid precipitates, allow the solution to stand at room temperature in an open atmosphere until the solvent evaporates completely to yield a solid.

[0206] 6. Solution vapor diffusion method

[0207] Weigh approximately 15 mg of sample and dissolve it in a good solvent. Place the clear solution in a poor solvent atmosphere and let it stand at room temperature until solid precipitates. Remove the solution from the system with solid precipitation using a syringe and perform XRPD analysis on the wet sample.

[0208] 7. Solid gas diffusion method

[0209] About 15 mg of an amorphous sample was weighed and placed in a selected solvent atmosphere at room temperature for 14 days. The properties of the solid in the glass vial were regularly observed, and the solid was subjected to XRPD analysis.

[0210] 8. Thermal transfer method

[0211] Thermal crystallization was performed using an Instec HCS424GXY hot stage (Instec Inc., US). A 6-8 mg sample was placed on a glass slide on the hot stage and heated to the target temperature at a rate of 10°C / min. The temperature was kept constant for 10 min, and then naturally cooled to room temperature to obtain a solid.

[0212] 9. Competitive suspension experiment

[0213] Saturated solutions of cyclohexane at different temperatures (10-60°C) were prepared, and equal amounts of solids of different crystal forms were added to the saturated solutions. The samples were suspended and stirred for a certain period of time under the selected specific temperature conditions, and then centrifuged. The wet samples were characterized by XRPD.

[0214] 10. Stability study

[0215] A certain amount of sample (amorphous: about 10 mg; crystalline form P: about 20 mg) was weighed and placed in a weighing bottle. The sample was then placed under high temperature (60°C), high humidity (25°C / 92.5% RH), light (25°C / 4500 Lux), and accelerated conditions (40°C / 75% RH). Samples were taken on days 7 and 17 for XRPD characterization and HPLC testing.

[0216] 11. Solubility test

[0217] 11.1 pH Solubility Test

[0218] The preparation process of the pH buffer is shown in Table 19. Samples of different crystalline forms were added to the pH buffer and shaken at a constant temperature of 25°C for 24 hours. The sampled solutions were then filtered through a 0.22 μm aqueous filter. Samples with higher concentrations were appropriately diluted with diluent. The signal peak area of ​​the solution was measured using HPLC. Finally, the concentration of the compound in the solution was calculated based on the peak area, the HPLC standard curve of the raw material, and the dilution factor. Furthermore, the remaining liquid was centrifuged, and the remaining supernatant was collected for pH testing.

[0219] Table 19 Preparation process of pH buffer solution

[0220] 11.2 Biological media and water solubility test

[0221] The preparation process of the biological medium is shown in Table 20. Samples of different crystalline forms were added to the biological medium and water and shaken at 37°C for 24 hours. Samples were taken at 0.5, 2, and 24 hours. The sampled solutions were filtered through a 0.22 μm water filter. Some samples with higher concentrations were appropriately diluted with diluent. The signal peak area of ​​the solution was measured by HPLC. Finally, the concentration of the compound in the solution was calculated based on the peak area, the HPLC standard curve of the raw material, and the dilution factor. In addition, the pH value of the supernatant after 24 hours was tested, and the remaining solid was analyzed by XRPD.

[0222] Table 20 Preparation process of biological medium

[0223] Example 1 Preparation of the compound represented by formula (I)

[0224] Preparation of Compounds 1-4

[0225] Compound 1-1 (28.2 g, 96 mmol) was added to a three-necked flask and the atmosphere was replaced with nitrogen three times. Anhydrous ether (100 mL) was added to the flask, and methyl lithium (1.6 M, 120 mL, 192 mmol) was added dropwise at -78°C. The reaction system was stirred at -78°C for 5 minutes, then gradually warmed to 0°C and stirred in an ice bath for 3 hours. Compound 1-3 (15 g, 60 mmol) was then added to the reaction system, and stirring was continued at room temperature for 16 hours. After completion of the reaction, the reaction system was extracted with EtOAc (100 mL x 3). The organic phases were combined, dried, and concentrated to obtain the crude product, which was then purified by normal phase silica gel column chromatography (EtOAc / PE = 0-5%) to afford the title compound 1-4 (10 g) as a light yellow liquid in a 33% yield. 1 H NMR (400MHz, CDCl3) δ4.33 (q, J=7.2Hz, 2H), 2.44 (s, 6H), 1.36 (t, J=7.2Hz, 3H). 19 F NMR (376MHz, CDCl3) δ-109.15 (s, 2F).

[0226] Preparation of Compounds 1-6

[0227] Iron triacetylacetonate (2.2 g, 6.3 mmol) was added to a three-necked flask and the atmosphere was purged with nitrogen three times. Anhydrous THF (80 mL), compound 1-4 (10 g, 31.6 mmol), and TMEDA (1.5 g, 12.6 mmol) were then added sequentially to the flask. The reaction system was stirred for 5 minutes. A THF solution of the Grignard reagent 4-methoxyphenylmagnesium bromide (1-5) (0.5 M, 102 mL, 50.6 mmol) in THF was slowly added dropwise to the flask. The reaction was stirred at room temperature for 16 hours. After completion of the reaction, the reaction system was extracted with EtOAc (30 mL x 3). The organic phases were combined, dried, and concentrated to obtain the crude product. The crude product was then purified by a normal phase silica gel column (EtOAc / PE = 0-5%) to afford the title compound 1-6 (2.1 g) as a light yellow liquid in a 23% yield. 1 H NMR (400MHz, CDCl3) δ7.19–7.04(m,2H),6.92–6.77(m,2H),4.36(q,J=7.1Hz,2H),3.79(s,3H),2.16(s,6H),1.37(t,J=7.1Hz,3H). 19 F NMR (376MHz, CDCl3) δ-111.34 (s, 2F).

[0228] Preparation of Compound 1-8

[0229] Compound 1-7 (1.1 g, 5.6 mmol) was added to a three-necked flask and the atmosphere was replaced with nitrogen three times. Anhydrous ether (15 mL) was added to the flask, and n-butyl lithium (1.6 M, 3.5 mL, 5.6 mmol) was added dropwise at -78°C. The reaction system was stirred at -78°C for 45 minutes, and then a solution of compound 1-6 (1.5 g, 5.1 mmol) in anhydrous ether (10 mL) was added dropwise and stirred for 1 hour. After completion of the reaction, the reaction system was quenched with saturated ammonium chloride solution (5 mL) and extracted with EtOAc (20 mL x 3). The organic phases were combined, dried, and concentrated to obtain the crude product, which was separated and purified by normal phase silica gel column chromatography (EtOAc / PE = 0-5%) to afford the title compound 1-8 (1.6 g) as a yellow solid in an 86% yield. 1 H NMR (400MHz, CDCl3) δ7.92–7.77(m,1H),7.18–7.06(m,2H),7.03–6.88(m,2H),6.88–6.80(m,2H),3.79(s,3H),2.21(s,6H). 19F NMR (376MHz, CDCl3) δ -99.65 (d, J = 13.4Hz, 1F), -103.94 (q, J = 13.8Hz, 1F), -107.21 (d, J = 14.8Hz, 2F).

[0230] Preparation of compound 2-1

[0231] Compound 1-8 (1.8 g, 4.95 mmol) was placed in a microwave tube, followed by acetic acid (5 mL) and aqueous hydrogen bromide (48 wt.% in H2O, 5 mL). The tube was sealed and reacted at 95°C for 16 hours. After cooling, the mixture was spin-dried and extracted with EtOAc (30 mL x 3). The organic phases were combined, dried, and concentrated to obtain the crude product. This was then separated and purified on a normal phase silica gel column (EtOAc / PE = 0-30%) to afford the title compound 2-1 (1.3 g) as a brown-yellow liquid in a 72% yield. LC-MS (ESI): m / z 348.8 [MH] - .

[0232] Preparation of compound 20-1

[0233] Compound 2-1 (1.2 g, 3.43 mmol) was dissolved in a mixture of dichloromethane (15 mL) and water (15 mL). Trimethylsulfoxide iodide (3.02 g, 13.7 mmol) and sodium hydroxide (549 mg, 13.7 mmol) were added, and the reaction system was refluxed for 16 hours. After cooling to room temperature, the reaction system was adjusted to pH 6-7 with dilute hydrochloric acid. The mixture was extracted with DCM (20 mL x 3). The organic phases were combined, dried, and concentrated to obtain the crude product. The crude product was separated and purified by normal phase silica gel column chromatography (EtOAc / PE = 0-10%) to obtain the title compound 20-1 (1.17 g, 94% yield) as a light yellow oil. LC-MS(ESI):m / z 363.0[MH]-.1H NMR (400MHz, DMSO-d6) δ9.34(s,1H),7.67(td,J=8.5,6.5Hz,1H),7.35(ddd,J=10.5,9.3,2.6Hz,1H),7.16(tdd,J=8. 5,2.6,0.9Hz,1H),7.02–6.93(m,2H),6.74–6.63(m,2H),3.40–3.36(m,1H),3.11–3.05(m,1H),2.03–1.94(m,6H).19F NMR(376MHz, DMSO-d6)δ-107.77–-107.88(m,1F),-108.07–-108.22(m,1F),-108.71–-108.81(m,1F),-108.93–-109.06(m,1F).

[0234] Preparation of compound 20

[0235] Compound 20-1 (1.17 g, 3.21 mmol) was dissolved in DMF (10 mL), and compound 1-H tetrazolium (225 mg, 12.9 mmol) and potassium carbonate (444 mg, 12.9 mmol) were added, respectively. The reaction system was stirred at 80°C for 16 hours under sealed conditions. After cooling, the reaction solution was filtered, and the crude filtrate was purified by preparative separation (mobile phase: A: 0.1% formic acid in water; B: acetonitrile; column: Agilent 10Prep-C18 250×21.2 mm; column temperature: 25°C; gradient: 40%-60% acetonitrile in 12 min; flow rate: 30 mL / min) to obtain the title compound 20 (500 mg, 36% yield, containing a pair of enantiomers).

[0236] Compound 20: LC-MS (ESI): m / z 435.2 [M+H]+. 1H NMR (400 MHz, DMSO-d6) δ9.31 (br.s, 1H), 9.14 (s, 1H), 7.53 (m, 1H), 7.28 (m, 1H), 7.16 (s, 1H), 7.00 (m, 1H), 6.96–6.84 (m, 2H), 6.67–6.58 (m, 2H), 5.42 (d, J = 12 Hz, 1H), 5.01 (d, J = 12 Hz, 1H), 1.94 (dd, J = 9.5, 1.7 Hz, 3H), 1.72 (dd, J = 9.5, 1.7 Hz, 3H).19F NMR (376MHz, DMSO-d6) δ-102.85–-103.32(m,1F),-109.01–-109.42(m,2F),-109.67(d,J=9.2Hz,1F).

[0237] Preparation of compound 51

[0238] Compound 20 (80 mg, 0.18 mmol) was dissolved in acetonitrile (5 mL), and potassium carbonate (51 mg, 0.37 mmol) was added with stirring. After 5 minutes of reaction, 1,1,1-trifluoro-2,3-epoxypropane (31 mg, 0.28 mmol) was added, and the reaction was stirred at 50°C for 16 hours. The reaction solution was filtered, and the crude filtrate was purified by preparative separation (preparative method: column: Agilent 10Prep-C18 250x21.2 mm; column temperature: 25°C; mobile phase: water (0.1% TFA)-acetonitrile; mobile phase acetonitrile ratio: 50%-70% in 12 minutes; flow rate: 30 mL / min) to obtain the title compound 51 (62 mg, yield: 62%, containing two pairs of enantiomers).

[0239] Compound 51: LC-MS (ESI): m / z 547.2 [M+H] +. 1H NMR (400 MHz, DMSO-d6) δ9.13 (s, 1H), 7.54 (td, J = 9.0, 6.7 Hz, 1H), 7.28 (ddd, J = 12.0, 9.0, 2.6 Hz, 1H), 7.15 (s, 1H), 7.09–6.96 (m, 3H), 6.92–6.82 (m, 2H), 6.63 (d, J = 6.6 Hz ,1H),5.42(d,J=14.5Hz,1H),5.01(d,J=14.5Hz,1H),4.35(dt,J=11.3,6.8Hz,1H),4 .12(m,1H),4.01(m,1H),1.98(dd,J=9.4,1.7Hz,3H),1.76(dd,J=9.4,1.7Hz,3H).19F NMR(376MHz, DMSO-d6)δ-76.06(s,3F),-102.96–-103.17(m,1F),-109.22–-109.32(m,2F),-109.63(d,J=9.2Hz,1F).

[0240] Preparation of compounds of formula (I)

[0241] Compound 51 (62 mg) was subjected to SFC preparative chiral separation (preparative separation method, instrument model: MGⅡ preparative SFC (SFC-14); chromatographic column model: ChiralPak AD, 250×30 mm ID, 5 μm; mobile phase: A: CO2 B: isopropanol; elution gradient: B 20%; flow rate: 70 mL / min; column pressure: 100 bar; column temperature: 38°C; detection wavelength: 220 nm; cycle: ~4 min) to obtain the compound of formula (I) (11 mg).

[0242] Compound of formula (I): LC-MS (ESI): 547.2 [M+H]+. Chiral analysis method (Chromatographic column model: ChiralPak AD-3, 150×4.6 mm ID, 3 μm; Mobile phase: A: CO2B: Isopropanol (0.05% DEA); Elution gradient: Mobile phase: 5% B to 40% B over 5 minutes, maintained at 40% B for 2.5 minutes, then equilibrated at 5% B for 2.5 minutes; Flow rate: 2.5 mL / min; Column temperature: 35°C; Column pressure: 100 bar; Detection wavelength: 220 nm; RT = 4.257 min). 1H NMR(400MHz, DMSO-d6)δ9.13(s,1H),7.54(td,J=9.0,6.6Hz,1H),7.36–7.19(m,1H),7.15( s,1H),7.06–7.03(m,2H),7.03–6.98(m,1H),6.93–6.79(m,2H),6.63(d,J=6.6Hz,1H),5.42 (d,J=14.6Hz,1H),5.01(d,J=14.6Hz,1H),4.44–4.25(m,1H),4.11(dd,J=10.6,4.2Hz,1H) ,4.01(dd,J=10.6,6.4Hz,1H),1.98(dd,J=9.4,1.6Hz,3H),1.76(dd,J=9.4,1.6Hz,3H).19F NMR(376MHz, DMSO-d6)δ-76.06(s,3F),-102.96–-103.17(m,1F),-109.22–-109.32(m,2F),-109.64(d,J=9.6Hz,1F).

[0243] Example 2 Minimum Inhibitory Concentration (MIC) Test of the Compound of Formula (I) on Fungal Growth

[0244] (1) Main reagents:

[0245] RPMI1640 culture medium: Brand: Gibco, Product No.: 31800-014

[0246] Sabouraud dextrose agar (SDA): Brand: Haibo, Product No.: HB0253-81

[0247] Voriconazole: Brand: Adamas, Product Number: 22105A

[0248] Amphotericin B: Brand: Abcam, Catalog Number: ab141199

[0249] (2) Fungal strains are shown in Table 21 below:

[0250] Table 21

[0251] (3) Test method:

[0252] MIC testing was performed according to the guidelines and requirements of CLSI M27 (for yeasts) and M38 (for Aspergillus).

[0253] Prepare the strain: Streak the strain onto an SDA plate one day in advance using a glycerol stock stored at -80°C. Incubate at 35°C and 40-60% humidity for 18-24 hours. For Aspergillus fumigatus and Cryptococcus neoformans, streak the plate 3 and 2 days in advance, respectively.

[0254] Preparation of culture media and compounds: Prepare RPMI liquid culture medium with purified water, add 0.165 mol / L MOPS, and adjust the pH to 7.0. Sterilize with a 0.22 μm filter membrane and store at 4°C (for no more than 3 months). Autoclave 0.85% saline at 121°C for 30 minutes and store at room temperature (for no more than 1 week). Dissolve the compound in DMSO at 12.8 mg / mL and store at -20°C.

[0255] For yeast, pick 3-5 colonies from an SDA plate on the day of testing and thoroughly resuspend in 5 mL of sterile 0.85% saline. Measure the turbidity of the culture solution with a turbidimeter and adjust the turbidity to approximately 0.2. Dilute the culture solution 50-fold and then 20-fold (a total of 1000-fold) with RPMI 1640 medium to prepare the inoculum. The final inoculum concentration is 500-2500 CFU / mL.

[0256] For Aspergillus, take 5 mL of saline solution to cover the mycelium, gently scrape off the spores with a spreader, and then transfer the spore suspension to a sterile test tube. Pipette an appropriate amount of spore suspension and count the spores under a microscope using a hemocytometer. Use RPMI1640 medium to adjust the spore concentration to approximately 0.4-5 x 10 4 spores / mL.

[0257] Compounds were diluted in DMSO to a maximum concentration of 800 μg / mL (or 400 μg / mL) and serially diluted 10 times, two-fold, for a total of 11 concentrations. 2 μL of the serially diluted compound was transferred to the corresponding wells of a 96-well plate. 198 μL of the inoculum was then transferred to the test plate and incubated at 35°C for 24 hours (48 hours for Aspergillus fumigatus and 72 hours for Cryptococcus neoformans, respectively).

[0258] (4) MIC assessment:

[0259] After incubation, fungal growth was visually observed. The lowest compound concentration that inhibited yeast growth by ≥50% (100% inhibition for Aspergillus) was defined as the minimum inhibitory concentration (MIC) (μg / mL). A magnifying glass or reading OD530nm can be used to assist in determining the MIC. The test plates were photographed and recorded for archiving. The results are shown in Table 22 below.

[0260] Table 22: In vitro antifungal activity results of compounds of formula (I) MIC (μg / mL)

[0261] Example 3 Preparation of Form A

[0262] 20.3 mg of the compound represented by formula (I) was weighed and added to 1.1 ml of chloroform to prepare a clear solution. After the solid precipitated, it was filtered first. The filtered solution was left to stand open at room temperature until the solvent was completely evaporated to obtain Form A.

[0263] Example 4 Preparation of Form B

[0264] A 15 mg sample of the compound represented by formula (I) was weighed, and 0.07 ml of ethyl acetate was added dropwise at room temperature to completely dissolve the sample. The solution was then added dropwise to 0.7 ml of n-heptane. After stirring for 1 hour, the precipitated solid was centrifuged and dried under vacuum at room temperature to obtain Form B. The clarified solution was further stirred for 24 hours, the precipitated solid was centrifuged, and dried under vacuum at room temperature to obtain Form B.

[0265] Example 5 Preparation of Form C

[0266] A 14.9 mg sample of the compound represented by formula (I) was weighed, and 0.06 ml of butyl formate was added dropwise at room temperature to completely dissolve the sample. 0.12 ml of toluene was added dropwise to the solution. After stirring at room temperature for 1 hour, the precipitated solid was centrifuged and dried in vacuo at room temperature to obtain Form C. The clarified solution was further stirred for 24 hours, the precipitated solid was centrifuged, and dried in vacuo at room temperature to obtain Form C.

[0267] Example 6 Preparation of Form D

[0268] A 15.5 mg sample of the compound represented by formula (I) was weighed, and 1.16 ml of chloroform was added dropwise at room temperature to completely dissolve the sample. 1.00 ml of n-heptane was added dropwise to the solution. After stirring at room temperature for 1 hour, the precipitated solid was centrifuged and dried in vacuo at room temperature to obtain Form D. The clarified solution was further stirred for 24 hours, the precipitated solid was centrifuged, and dried in vacuo at room temperature to obtain Form D.

[0269] Example 7 Preparation of Form E

[0270] A 15.4 mg sample of the compound represented by formula (I) was weighed, and 0.07 ml of dioxane was added dropwise at room temperature to completely dissolve the sample. The solution was then added dropwise to 0.7 ml of water. After stirring for 1 hour, the precipitated solid was centrifuged and dried in vacuo at room temperature to obtain Form E. The clarified solution was further stirred for 24 hours, the precipitated solid was centrifuged, and dried in vacuo at room temperature to obtain Form E.

[0271] Example 8 Preparation of Form F

[0272] A 14.8 mg sample of the compound represented by formula (I) was weighed, and 0.07 ml of chloroform was added dropwise at room temperature to completely dissolve the sample. The solution was then added dropwise to 0.7 ml of cyclohexane. After stirring for 1 hour, the precipitated solid was centrifuged and dried in vacuo at room temperature to obtain Form F. The clarified solution was further stirred for 24 hours, the precipitated solid was centrifuged, and dried in vacuo at room temperature to obtain Form F.

[0273] Example 9 Preparation of Form G

[0274] A 15.1 mg sample of the compound represented by formula (I) was weighed, and 0.06 ml of ether was added dropwise at room temperature to completely dissolve the sample. 0.06 ml of n-heptane was added dropwise to the solution. After stirring at room temperature for 1 hour, the precipitated solid was centrifuged and dried in vacuo at room temperature to obtain Form G. The clarified solution was further stirred for 24 hours, the precipitated solid was centrifuged, and dried in vacuo at room temperature to obtain Form G.

[0275] Example 10 Preparation of Form H

[0276] A 15.1 mg sample of the compound represented by formula (I) was weighed, and 0.06 ml of ethyl formate was added dropwise at room temperature to completely dissolve the sample. 0.06 ml of n-heptane was added dropwise to the solution. After stirring at room temperature for 1 hour, the precipitated solid was centrifuged and dried in vacuo at room temperature to obtain Form H. The clarified solution was further stirred for 24 hours, the precipitated solid was centrifuged, and dried in vacuo at room temperature to obtain Form H.

[0277] Example 11 Preparation of Form I

[0278] 20.3 mg of the compound represented by formula (I) was added to 1.3 ml of dichloromethane to prepare a clear solution. After the solid precipitated, it was filtered first. The filtered solution was left to stand open at room temperature until the solvent was completely evaporated to obtain Form I.

[0279] Example 12 Preparation of Form J

[0280] A 15.3 mg sample of the compound represented by formula (I) was weighed, and 0.07 ml of isopropyl acetate was added dropwise at room temperature to completely dissolve the sample. The solution was then added dropwise to 0.7 ml of cyclohexane. After stirring for 1 hour, the precipitated solid was centrifuged and dried in vacuo at room temperature to obtain Form J. The clarified solution was further stirred for 24 hours, the precipitated solid was centrifuged, and dried in vacuo at room temperature to obtain Form J.

[0281] Example 13 Preparation of Form K

[0282] 15.1 mg of the compound represented by formula (I) was added to 0.05 ml of chloroform and 0.45 ml of n-heptane to form a suspension. After suspending and stirring at room temperature for 2 days, the suspension was centrifuged and the solid was vacuum dried at room temperature to obtain Form K.

[0283] Example 14 Preparation of Form L

[0284] 15.5 mg of the compound represented by formula (I) was added to 0.05 ml of ethyl formate and 0.45 ml of cyclohexane solvent to form a suspension. The suspension was stirred at room temperature for 2 days. The suspension was centrifuged and the solid was dried under vacuum at room temperature to obtain Form L.

[0285] Example 15 Preparation of Form M

[0286] 45.7 mg of the compound represented by formula (I) was added to 0.15 ml of dichloromethane and 1.35 ml of cyclohexane solvent to form a suspension. After suspension and stirring at 10° C. for 24 h, the suspension was centrifuged and the solid was dried in vacuo at 40° C. to obtain Form M.

[0287] Example 16 Preparation of Form N

[0288] Weigh 15.0 mg of the compound represented by formula (I) and mix it with 1.0 ml of cyclohexane at 50°C to form a suspension.

[0289] A turbid solution was obtained. 1.4 ml of chloroform, preheated to 50°C, was gradually added dropwise. The solution was transferred to room temperature and cooled. The solution was allowed to stand at room temperature for at least 2 hours. The precipitated solid was centrifuged and then dried under vacuum at room temperature to obtain Form N.

[0290] Example 17 Preparation of Form O

[0291] 15.6 mg of an amorphous sample of the compound represented by formula (I) was added to 0.05 ml of dichloromethane and 0.45 ml of n-heptane to form a suspension. After suspension and stirring at 10° C. for 24 hours, the suspension was centrifuged and the solid was vacuum dried at room temperature to obtain Form O.

[0292] Example 18 Preparation of Form P

[0293] A 781.4 mg sample of the compound represented by Formula (I) was weighed and added to 26.0 mL of a binary solvent of methyl tert-butyl ether / n-heptane (v / v, 1:9). The mixture was suspended and stirred at room temperature for 48 hours. The supernatant was removed by centrifugation, and the solid was dried in vacuo at 40°C for 1 day. The dried solid was added to 21.5 mL of a binary solvent of methyl tert-butyl ether / n-heptane (v / v, 1:9), suspended and stirred at room temperature for 24 hours. The supernatant was removed by centrifugation, and the solid was dried in vacuo at 40°C for 1 day to obtain 699.3 mg of Form P.

[0294] Example 19 Preparation of amorphous

[0295] A 436.5 mg sample of the compound represented by formula (I) was weighed and dissolved in 4.5 mL of ethanol. Insoluble impurities were filtered to remove the sample. Rotary evaporation afforded a fluffy white solid, which was then dried under vacuum at room temperature for 4 days. The resulting sample was added to 2.0 mL of dichloromethane, suspended and stirred at room temperature for 24 hours, then dried under vacuum at room temperature overnight, and then dried under vacuum at 40°C for 2 days to yield 280.0 mg of an amorphous form.

[0296] Example 20 Solubility Test of Form P

[0297] The solubility of Form P in six solvents was determined, and the results are shown in Table 23. According to the solubility test results, Form P was readily soluble in ethanol, acetone, and ethyl acetate (>100 mg / mL); and soluble in acetonitrile, dichloromethane, and tetrahydrofuran (>10 mg / mL). During the solubility test, Form P was observed to be substantially soluble in 0.1 mL of ethanol, acetone, ethyl acetate, acetonitrile, and tetrahydrofuran, respectively. Particulate matter adhered to the wall of the EP tube in the solution. As the solvent continued to be added, the particulate matter gradually dissolved completely. Form P was substantially soluble in 1.1 mL of dichloromethane. With continued addition of dichloromethane, no signs of reduction in the flocculent matter in the solution were observed.

[0298] Table 23 Solubility test results of Form P

[0299] Example 21 Stability Study

[0300] Stability studies were conducted on the amorphous form and Form P under conditions of high temperature (60°C), high humidity (25°C / 92.5% RH), illumination (25°C / 4500 Lux), and accelerated exposure (40°C / 75% RH). Samples were taken for XRPD characterization and HPLC analysis after 7 and 17 days, respectively. The results are shown in Table 24, Figures 39, and 40. XRPD results showed that both the amorphous form and Form P were stable under these conditions for 17 days, with no form transition. Deliquescence was observed under accelerated conditions. HPLC results showed that the chemical purity of the amorphous form and Form P remained unchanged after 17 days under these conditions.

[0301] Table 24 Stability study results

[0302] Table 25 HPLC purity analysis results of amorphous stability samples

[0303] Table 26 HPLC purity analysis results of Form P stability samples

[0304] Example 22 pH Solubility Test

[0305] The solubility of amorphous and crystalline P in buffer solutions at different pH values ​​was determined using the experimental method described in General Test Methods 11.1, and the corresponding results are shown in Table 27. The results showed that the solubility of amorphous and crystalline P in buffer solutions at different pH values ​​was very low and was not detected.

[0306] Table 27 pH solubility test results

[0307] Example 23 Biological media and water solubility test

[0308] Dynamic solubility tests were conducted on amorphous and crystalline forms of P in three biological media (FaSSIF, FeSSIF, and FaSSGF) and in water. The experimental methods are described in General Test Methods 11.2, and the corresponding results are shown in Table 28 and Figures 41 and 42. The results showed that the solubility of the amorphous form in FaSSIF and FeSSIF, as well as the crystalline form in FeSSIF, decreased over time. The 24-hour solubility of amorphous and crystalline forms of P in FeSSIF was greater than that in FaSSIF. No solubility was detected in FaSSGF or water. After the solubility tests, the remaining solid crystalline form in both the biological media and water remained unchanged.

[0309] Table 28 Dynamic solubility test in biological media

[0310] In the description of this specification, the reference terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" mean that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art can combine and combine different embodiments or examples described in this specification and features of different embodiments or examples without contradiction.

[0311] Although the embodiments of the present invention have been shown and described above, it will be understood that the above embodiments are illustrative and are not to be construed as limitations on the present invention. A person skilled in the art may change, modify, replace and modify the above embodiments within the scope of the present invention.

Claims

1. Crystalline Form A of the Compound of Formula (I) It is characterized by: Using Cu-Kα radiation, the X-ray powder diffraction pattern of the crystalline form A has characteristic diffraction peaks at the following 2θ angles: 3.76±0.2°, 5.2±0.2°, 13.75±0.2°, 16.97±0.2°, 17.67±0.2°, and 19.75±0.2°; Optionally, the X-ray powder diffraction pattern of the crystalline form A has characteristic diffraction peaks at the following 2θ angles: 3.76±0.2°, 5.2±0.2°, 5.82±0.2°, 13.75±0.2°, 14.7±0.2°, 16.97±0.2°, 17.67±0.2°, 18.41±0.2°, 19.75±0.2°, 21.09±0.2°; Optionally, the X-ray powder diffraction pattern of the crystalline form A has characteristic diffraction peaks at the following 2θ angles: 3.76±0.2°, 5.2±0.2°, 5.82±0.2°, 13.07±0.2°, 13.75±0.2°, 14.7±0.2°, 15.85±0.2°, 16.97±0.2°, 17.67±0.2°, 18.41±0.2°, 19.23±0.2°, 19.75±0.2°, 21.09±0.2°, 21.87±0.2°, and 22.92±0.2°; Optionally, the X-ray powder diffraction pattern of the crystalline form A has an X-ray powder diffraction pattern substantially as shown in FIG1 .

2. Form B of the compound represented by formula (I), characterized in that: Using Cu-Kα radiation, the X-ray powder diffraction pattern of the crystalline form B has characteristic diffraction peaks at the following 2θ angles: 11.92±0.2°, 16.31±0.2°, 17.75±0.2°, 18.74±0.2°, 19.56±0.2°, and 21.72±0.2°; Optionally, the X-ray powder diffraction pattern of the crystalline form B has characteristic diffraction peaks at the following 2θ angles: 9.88±0.2°, 11.92±0.2°, 16.31±0.2°, 17.19±0.2°, 17.75±0.2°, 18.74±0.2°, 19.56±0.2°, 20.59±0.2°, 21.72±0.2°, 23.68±0.2°; Optionally, the X-ray powder diffraction pattern of the crystalline form B has characteristic diffraction peaks at the following 2θ angles: 9.88±0.2°, 10.89±0.2°, 11.92±0.2°, 13.11±0.2°, 14.84±0.2°, 16.31±0.2°, 17.19±0.2°, 17.75±0.2°, 18.74±0.2°, 19.56±0.2°, 20.59±0.2°, 21.27±0.2°, 21.72±0.2°, 22.84±0.2°, 23.68±0.2°; Optionally, the X-ray powder diffraction pattern of Form B has an X-ray powder diffraction pattern substantially as shown in FIG3 .

3. Form C of the compound represented by formula (I), characterized in that: Using Cu-Kα radiation, the X-ray powder diffraction pattern of the crystalline form C has characteristic diffraction peaks at the following 2θ angles: 10.15±0.2°, 11.26±0.2°, 18.24±0.2°, 20.34±0.2°, 20.92±0.2°, and 22.59±0.2°; Optionally, the X-ray powder diffraction pattern of the crystalline form C has characteristic diffraction peaks at the following 2θ angles: 10.15±0.2°, 11.26±0.2°, 14.27±0.2°, 16.57±0.2°, 17.75±0.2°, 18.24±0.2°, 20.34±0.2°, 20.92±0.2°, 22.59±0.2°, 27.33±0.2°; Optionally, the X-ray powder diffraction pattern of the crystalline form C has characteristic diffraction peaks at the following 2θ angles: 7.04±0.2°, 10.15±0.2°, 10.97±0.2°, 11.26±0.2°, 14.27±0.2°, 16.57±0.2°, 17.75±0.2°, 18.24±0.2°, 20.34±0.2°, 20.92±0.2°, 22.59±0.2°, 23.78±0.2°, 24.87±0.2°, 25.97±0.2°, 27.33±0.2°; Optionally, the X-ray powder diffraction pattern of Form C has an X-ray powder diffraction pattern substantially as shown in FIG5 .

4. Form D of the compound represented by formula (I), characterized in that: Using Cu-Kα radiation, the X-ray powder diffraction pattern of the crystalline form D has characteristic diffraction peaks at the following 2θ angles: 4.96±0.2°, 6.65±0.2°, 8.93±0.2°, 13.11±0.2°, 13.85±0.2°, and 17.19±0.2°; Optionally, the X-ray powder diffraction pattern of the crystalline form D has characteristic diffraction peaks at the following 2θ angles: 4.34±0.2°, 4.96±0.2°, 6.65±0.2°, 8.93±0.2°, 13.11±0.2°, 13.85±0.2°, 17.19±0.2°, 17.95±0.2°, 18.84±0.2°, 20.01±0.2°; Optionally, the X-ray powder diffraction pattern of the crystalline form D has characteristic diffraction peaks at the following 2θ angles: 4.34±0.2°, 4.96±0.2°, 6.65±0.2°, 8.93±0.2°, 13.11±0.2°, 13.85±0.2°, 14.54±0.2°, 15.89±0.2°, 17.19±0.2°, 17.95±0.2°, 18.84±0.2°, 19.4±0.2°, 20.01±0.2°, 22.16±0.2°, 22.86±0.2°; Optionally, the X-ray powder diffraction pattern of the crystalline form D has an X-ray powder diffraction pattern substantially as shown in FIG7 .

5. Crystalline Form E of the compound represented by formula (I), characterized in that: Using Cu-Kα radiation, the X-ray powder diffraction pattern of the crystalline form E has characteristic diffraction peaks at the following 2θ angles: 10.42±0.2°, 12.6±0.2°, 16.59±0.2°, 18.24±0.2°, 20.22±0.2°, and 22.42±0.2°; Optionally, the X-ray powder diffraction pattern of the crystalline form E has characteristic diffraction peaks at the following 2θ angles: 10.42±0.2°, 12.6±0.2°, 13.5±0.2°, 16.59±0.2°, 17.71±0.2°, 18.24±0.2°, 20.22±0.2°, 20.88±0.2°, 22.42±0.2°, 24.11±0.2°; Optionally, the X-ray powder diffraction pattern of the crystalline form E has characteristic diffraction peaks at the following 2θ angles: 3.76±0.2°, 10.42±0.2°, 12.6±0.2°, 13.5±0.2°, 14.51±0.2°, 15.23±0.2°, 16.59±0.2°, 17.71±0.2°, 18.24±0.2°, 20.22±0.2°, 20.88±0.2°, 21.44±0.2°, 22.42±0.2°, 23.5±0.2°, 24.11±0.2°; Optionally, the X-ray powder diffraction pattern of the crystalline Form E has an X-ray powder diffraction pattern substantially as shown in FIG9 .

6. Form F of the compound represented by formula (I), characterized in that: Using Cu-Kα radiation, the X-ray powder diffraction pattern of the crystalline form F has characteristic diffraction peaks at the following 2θ angles: 11.94±0.2°, 15.75±0.2°, 18.06±0.2°, 19.27±0.2°, 20.47±0.2°, and 21.39±0.2°; Optionally, the X-ray powder diffraction pattern of the crystalline form F has characteristic diffraction peaks at the following 2θ angles: 3.35±0.2°, 4.11±0.2°, 10.09±0.2°, 11.24±0.2°, 11.94±0.2°, 15.75±0.2°, 18.06±0.2°, 19.27±0.2°, 20.47±0.2°, 21.39±0.2°; Optionally, the X-ray powder diffraction pattern of the crystalline form F has characteristic diffraction peaks at the following 2θ angles: 3.35±0.2°, 4.11±0.2°, 5.18±0.2°, 5.7±0.2°, 10.09±0.2°, 11.24±0.2°, 11.94±0.2°, 15.75±0.2°, 16.59±0.2°, 18.06±0.2°, 19.27±0.2°, 20.47±0.2°, 21.39±0.2°, 22.46±0.2°, 24.24±0.2°; Optionally, the X-ray powder diffraction pattern of Form F has an X-ray powder diffraction pattern substantially as shown in FIG11 .

7. Form G of the compound represented by formula (I), characterized in that: Using Cu-Kα radiation, the X-ray powder diffraction pattern of the crystalline form G has characteristic diffraction peaks at the following 2θ angles: 5.62±0.2°, 10.58±0.2°, 11.65±0.2°, 14.62±0.2°, 17.67±0.2°, and 21.13±0.2°; Optionally, the X-ray powder diffraction pattern of the crystalline form G has characteristic diffraction peaks at the following 2θ angles: 5.62±0.2°, 10.58±0.2°, 11.65±0.2°, 14.62±0.2°, 15.34±0.2°, 17.67±0.2°, 19.95±0.2°, 20.51±0.2°, 21.13±0.2°, 21.66±0.2°; Optionally, the X-ray powder diffraction pattern of the crystalline form G has characteristic diffraction peaks at the following 2θ angles: 5.62±0.2°, 9.34±0.2°, 9.8±0.2°, 10.58±0.2°, 11.65±0.2°, 14.62±0.2°, 15.34±0.2°, 17.67±0.2°, 18.61±0.2°, 19.95±0.2°, 20.51±0.2°, 21.13±0.2°, 21.66±0.2°, 23.33±0.2°, 25.02±0.2°; Optionally, the X-ray powder diffraction pattern of Form G has an X-ray powder diffraction pattern substantially as shown in FIG13 .

8. Form H of the compound represented by formula (I), characterized in that: Using Cu-Kα radiation, the X-ray powder diffraction pattern of the crystalline form H has characteristic diffraction peaks at the following 2θ angles: 10.46±0.2°, 12.47±0.2°, 16.29±0.2°, 18.41±0.2°, 20.26±0.2°, and 21.02±0.2°; Optionally, the X-ray powder diffraction pattern of the crystalline form H has characteristic diffraction peaks at the following 2θ angles: 10.46±0.2°, 11.34±0.2°, 12.47±0.2°, 16.29±0.2°, 17.89±0.2°, 18.41±0.2°, 19.5±0.2°, 20.26±0.2°, 21.02±0.2°, 22.42±0.2°; Optionally, the X-ray powder diffraction pattern of the crystalline form H has characteristic diffraction peaks at the following 2θ angles: 10.46±0.2°, 11.34±0.2°, 12.47±0.2°, 13.53±0.2°, 16.29±0.2°, 16.97±0.2°, 17.89±0.2°, 18.41±0.2°, 19.07±0.2°, 19.5±0.2°, 20.26±0.2°, 21.02±0.2°, 22.42±0.2°, 24.01±0.2°, 25.53±0.2°; Optionally, the X-ray powder diffraction pattern of the crystalline Form H has an X-ray powder diffraction pattern substantially as shown in FIG15 .

9. Crystalline Form I of the compound represented by formula (I), characterized in that: Using Cu-Kα radiation, the X-ray powder diffraction pattern of the crystalline form I has characteristic diffraction peaks at the following 2θ angles: 9.84±0.2°, 10.37±0.2°, 11.51±0.2°, 20.24±0.2°, 20.71±0.2°, and 22.96±0.2°; Optionally, the X-ray powder diffraction pattern of the crystalline form I has characteristic diffraction peaks at the following 2θ angles: 9.84±0.2°, 10.37±0.2°, 11.51±0.2°, 14.27±0.2°, 17.95±0.2°, 18.3±0.2°, 20.24±0.2°, 20.71±0.2°, 21.25±0.2°, 22.96±0.2°; Optionally, the X-ray powder diffraction pattern of the crystalline Form I has an X-ray powder diffraction pattern substantially as shown in Figure 17.

10. Crystalline Form J of the compound represented by formula (I), characterized in that: Using Cu-Kα radiation, the X-ray powder diffraction pattern of the crystalline form J has characteristic diffraction peaks at the following 2θ angles: 11.67±0.2°, 16.08±0.2°, 16.68±0.2°, 18.86±0.2°, 19.35±0.2°, and 23.74±0.2°; Optionally, the X-ray powder diffraction pattern of the crystalline form J has characteristic diffraction peaks at the following 2θ angles: 9.67±0.2°, 10.91±0.2°, 11.67±0.2°, 16.08±0.2°, 16.68±0.2°, 17.21±0.2°, 18.86±0.2°, 19.35±0.2°, 21.27±0.2°, 23.74±0.2°; Optionally, the X-ray powder diffraction pattern of the crystalline form J has characteristic diffraction peaks at the following 2θ angles: 5.49±0.2°, 6.3±0.2°, 9.67±0.2°, 10.91±0.2°, 11.67±0.2°, 12.87±0.2°, 14.68±0.2°, 16.08±0.2°, 16.68±0.2°, 17.21±0.2°, 18.86±0.2°, 19.35±0.2°, 20.32±0.2°, 21.27±0.2°, 23.74±0.2°; Optionally, the X-ray powder diffraction pattern of Form J has an X-ray powder diffraction pattern substantially as shown in FIG19 .

11. Crystalline Form K of the compound represented by formula (I), characterized in that: Using Cu-Kα radiation, the X-ray powder diffraction pattern of the crystalline form K has characteristic diffraction peaks at the following 2θ angles: 12.04±0.2°, 15.85±0.2°, 18.18±0.2°, 19.31±0.2°, 19.56±0.2°, and 21.48±0.2°; Optionally, the X-ray powder diffraction pattern of the crystalline form K has characteristic diffraction peaks at the following 2θ angles: 11.42±0.2°, 12.04±0.2°, 15.85±0.2°, 16.64±0.2°, 18.18±0.2°, 19.31±0.2°, 19.56±0.2°, 20.57±0.2°, 21.48±0.2°, 24.28±0.2°; Optionally, the X-ray powder diffraction pattern of the crystalline form K has characteristic diffraction peaks at the following 2θ angles: 5.76±0.2°, 10.17±0.2°, 11.42±0.2°, 12.04±0.2°, 15.85±0.2°, 16.64±0.2°, 18.18±0.2°, 18.72±0.2°, 19.31±0.2°, 19.56±0.2°, 20.57±0.2°, 21.48±0.2°, 22.51±0.2°, 24.28±0.2°, 25.6±0.2°; Optionally, the X-ray powder diffraction pattern of the crystalline Form K has an X-ray powder diffraction pattern substantially as shown in FIG. 21 .

12. Crystalline Form L of the compound represented by formula (I), characterized in that: Using Cu-Kα radiation, the X-ray powder diffraction pattern of the crystalline form L has characteristic diffraction peaks at the following 2θ angles: 10.42±0.2°, 12.43±0.2°, 16.27±0.2°, 18.18±0.2°, 20.08±0.2°, and 21±0.2°; Optionally, the X-ray powder diffraction pattern of the crystalline form L has characteristic diffraction peaks at the following 2θ angles: 10.42±0.2°, 11.28±0.2°, 12.43±0.2°, 13.48±0.2°, 16.27±0.2°, 18.18±0.2°, 20.08±0.2°, 21±0.2°, 22.36±0.2°, 23.91±0.2°; Optionally, the X-ray powder diffraction pattern of the crystalline form L has characteristic diffraction peaks at the following 2θ angles: 3.08±0.2°, 10.42±0.2°, 11.28±0.2°, 12.43±0.2°, 13.48±0.2°, 14.47±0.2°, 16.27±0.2°, 16.82±0.2°, 18.18±0.2°, 20.08±0.2°, 21±0.2°, 22.36±0.2°, 23.91±0.2°, 25.47±0.2°, 28.15±0.2°; Optionally, the X-ray powder diffraction pattern of the crystalline Form L has an X-ray powder diffraction pattern substantially as shown in Figure 23.

13. Crystalline Form M of the compound represented by formula (I), characterized in that: Using Cu-Kα radiation, the X-ray powder diffraction pattern of the crystalline form M has characteristic diffraction peaks at the following 2θ angles: 5.33±0.2°, 7.04±0.2°, 14.7±0.2°, 15.85±0.2°, 18.43±0.2°, and 21.11±0.2°; Optionally, the X-ray powder diffraction pattern of the crystalline form M has characteristic diffraction peaks at the following 2θ angles: 4.38±0.2°, 5.33±0.2°, 7.04±0.2°, 14.06±0.2°, 14.7±0.2°, 15.85±0.2°, 17.38±0.2°, 18.43±0.2°, 19.11±0.2°, 21.11±0.2°; Optionally, the X-ray powder diffraction pattern of the crystalline form M has characteristic diffraction peaks at the following 2θ angles: 4.38±0.2°, 4.87±0.2°, 5.33±0.2°, 7.04±0.2°, 10.6±0.2°, 14.06±0.2°, 14.7±0.2°, 15.85±0.2°, 17.38±0.2°, 18.43±0.2°, 19.11±0.2°, 19.58±0.2°, 21.11±0.2°, 21.78±0.2°, 27.78±0.2°; Optionally, the X-ray powder diffraction pattern of the crystalline Form M has an X-ray powder diffraction pattern substantially as shown in Figure 25.

14. Crystalline Form N of the compound represented by formula (I), characterized in that: Using Cu-Kα radiation, the X-ray powder diffraction pattern of the crystalline form N has characteristic diffraction peaks at the following 2θ angles: 4.9±0.2°, 12.7±0.2°, 13.5±0.2°, 16.62±0.2°, 17.38±0.2°, and 18.3±0.2°; Optionally, the X-ray powder diffraction pattern of the crystalline form N has characteristic diffraction peaks at the following 2θ angles: 3.17±0.2°, 4.48±0.2°, 4.9±0.2°, 5.12±0.2°, 12.7±0.2°, 13.5±0.2°, 16.62±0.2°, 17.38±0.2°, 18.3±0.2°, 20.92±0.2°; Optionally, the X-ray powder diffraction pattern of the crystalline form N has characteristic diffraction peaks at the following 2θ angles: 3.17±0.2°, 4.48±0.2°, 4.9±0.2°, 5.12±0.2°, 6.62±0.2°, 8.33±0.2°, 14.58±0.2°, 12.7±0.2°, 13.5±0.2°, 16.62±0.2°, 17.38±0.2°, 18.3±0.2°, 19.56±0.2°, 20.92±0.2°, 22.2±0.2°; Optionally, the X-ray powder diffraction pattern of the crystalline Form N has an X-ray powder diffraction pattern substantially as shown in Figure 27.

15. Crystalline Form O of the compound represented by formula (I), characterized in that: Using Cu-Kα radiation, the X-ray powder diffraction pattern of the crystalline form O has characteristic diffraction peaks at the following 2θ angles: 5.02±0.2°, 10.29±0.2°, 12.54±0.2°, 16.72±0.2°, 17.62±0.2°, and 20.45±0.2°; Optionally, the X-ray powder diffraction pattern of the crystalline form O has characteristic diffraction peaks at the following 2θ angles: 5.02±0.2°, 10.29±0.2°, 12.54±0.2°, 13.59±0.2°, 15.34±0.2°, 16.72±0.2°, 17.62±0.2°, 19.75±0.2°, 20.45±0.2°, 25.37±0.2°; Optionally, the X-ray powder diffraction pattern of the crystalline form O has characteristic diffraction peaks at the following 2θ angles: 5.02±0.2°, 10.29±0.2°, 12.54±0.2°, 13.59±0.2°, 14.25±0.2°, 15.34±0.2°, 16.72±0.2°, 17.62±0.2°, 19.75±0.2°, 20.45±0.2°, 20.9±0.2°, 22.61±0.2°, 23.33±0.2°, 25.37±0.2°, 26.79±0.2°; Optionally, the X-ray powder diffraction pattern of the crystalline Form O has an X-ray powder diffraction pattern substantially as shown in Figure 29.

16. The crystalline form P of the compound represented by formula (I), characterized in that: Using Cu-Kα radiation, the X-ray powder diffraction pattern of the crystalline form P has characteristic diffraction peaks at the following 2θ angles: 11.53±0.2°, 14.72±0.2°, 15.98±0.2°, 17.01±0.2°, 17.54±0.2°, and 19.5±0.2°; Optionally, the X-ray powder diffraction pattern of the crystalline form P has characteristic diffraction peaks at the following 2θ angles: 9.57±0.2°, 11.05±0.2°, 11.53±0.2°, 12.82±0.2°, 14.72±0.2°, 15.98±0.2°, 17.01±0.2°, 17.54±0.2°, 19.09±0.2°, 19.5±0.2°; Optionally, the X-ray powder diffraction pattern of the crystalline form P has characteristic diffraction peaks at the following 2θ angles: 9.57±0.2°, 11.05±0.2°, 11.53±0.2°, 12.82±0.2°, 14.72±0.2°, 15.98±0.2°, 17.01±0.2°, 17.54±0.2°, 19.09±0.2°, 19.5±0.2°, 20.24±0.2°, 20.88±0.2°, 21.43±0.2°, 22.14±0.2°, 23.89±0.2°; Optionally, the X-ray powder diffraction pattern of the crystalline form P has an X-ray powder diffraction pattern substantially as shown in Figure 31.

17. The amorphous form of the compound represented by formula (I), characterized in that: The amorphous form has an X-ray powder diffraction pattern substantially as shown in FIG. 35 using Cu-Kα radiation.